Inclusion of Women in the Mining Sector: Challenges and Opportunities Through Education - Selene Castañeda-Burciaga; Omar Alejandro Guirette-Barbosa; Martha Angélica Ramírez-Salazar; José María Celaya-Padilla; Leticia Isabel García-Estrada (Education Sciences)
Labor dynamics have changed in recent years, and women have increased their participation in various activities within the production and business industries. One of these sectors is mining, which presents both challenges and opportunities to promote gender equality and decent work. In light of this, the objective of the present study is to identify the limitations faced by women in the mining sector, framed within personal, family, social, and labor aspects, in relation to their educational level. Due to the nature of the study, a cross-sectional, descriptive, and non-experimental investigation was proposed. The sample consisted of more than 50 companies distributed throughout the Mexican Republic, with a total of 316 female workers in the mining sector. The main results show greater limitations in labor and family aspects. Moreover, educational levels directly affect how women perceive the impact of working in mining on the various areas in which they operate.